Exact Formulas of the Transition Probabilities of the Multi-Species Asymmetric Simple Exclusion Process - Eunghyun Lee (SIGMA, 2020)
We find the formulas of the transition probabilities of the N-particle multispecies asymmetric simple exclusion processes (ASEP), and show that the transition probabilities are written as a determinant when the order of particles in the final state is the same as the order of particles in the initial state.
Keywords: ASEP, multi-species ASEP, integrable probability